“Pride and Honour”: Indigenous Dance in New South Wales Schools - Wilson, Katie (Springer International Publishing, 2016)
In this chapter, I discuss the positioning of Indigenous dance performance in Australian school education where European knowledges and beliefs dominate educational policies and practices. The discussion about the role and the integration of indigenous dance within curriculum takes place in the context of research with Aboriginal and Torres Strait Islander students in schools in a regional area of the state of New South Wales. More than two centuries after colonisation, dispossession and attempted deculturation of Aboriginal and Torres Strait Islander peoples, the positive value of cultural learning and practices in education is acknowledged in policy and included in curricula as a means of engaging Indigenous students with dominant education. However, while schools welcome and acknowledge the significance of Indigenous students’ participation in dance performance, this activity and related acquisition of skills and knowledges by dancing students are not accredited academically.